A Five-Year strategic financial plan for COL Financial Group, Inc. - Delgado, Lizbeth B., Laosantos, Jennica T., Manalo, Patricia Jane M., Manglal-lan, Jeian Nicole B., Miralpes, Jennifer C., Rio, Renalyn R., Sucgang, Fatima Sheikah Ysabelle A. 4 0 16; 5
Introduction: COL Financing Group, Inc. was established and licensed by the SEC in 1999 and is a publicly listed company in the Philippine Stock Exchange (PSE), incorporated on August 16, 1999, for a singular purpose: to help every Filipino achieve a richer life. The company was envisioned to be the leading and fastest-growing online stockbroker in the Philippines that focused on tapping the underserved retail investor base in the stock market. In its pursuit of making investing easy and convenient for everyone, COL launched its proprietary online trading platform in 2001, offering real-time market information and direct market access, while providing the comprehensive stock market research and analysis necessary for its clients to make well-informed investment decisions. The business objective focuses on being the preferred source of financial services, a trusted provider of guidance and investment and a strong organization committed to delivering great value to its customers making their goal centralized to Our goal is to be Champion of the Filipino Investor. As a publicly listed stockbroker company, COL Financial Group, Inc. is a prominent entity in the realm of online stock brokerage. COL established its wholly-owned foreign subsidiary COL Securities (HK) Limited (COLHK) on June 20, 2001, to provide investors with online access to the Hong Kong stock market. This reach was further expanded in August 2014 when COLHK entered a non-disclosed broker account with Interactive Brokers (IB) which allowed its clients to trade electronically in global equity markets that included Japan, USA, Singapore, Germany, and China. In July 2015, continuing its drive to enable Filipinos to achieve their financial goals, COL launched the Philippines' first online mutual fund supermarket, COL Fund Source, giving investors access to a wide selection of the country's top mutual funds, with no sales-load or transaction fees. In 2019, COL set up its asset management firm, COL Investment Management, Inc. (CIMI), to create mutual funds that would address the different investment needs of COL's customer base. CIMI serves as the fund manager of two mutual funds, namely, COL Equity Index Unitized Mutual Fund, Inc. (CEIUMF) and COL Strategic Growth Equity Unitized Mutual Fund, Inc. (CSGEUMF) (formerly: COL Cash Management Unitized Mutual Fund, Inc.). Today, COL is one of the leading online stockbrokers in the Philippines, remaining committed to its objective of prosperity for the Filipino people, by providing easy access to the market and the knowledge they need to invest wisely.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2